2002
DOI: 10.3109/15622970209150600
|View full text |Cite
|
Sign up to set email alerts
|

The Activity of β-Hexosaminidase (uHex) and y-Glutamyi-transferase (uGGT) in Urine as Non-Invasive Markers of Chronic Alcohol Abuse: II. Opiate-Dependent Subjects Receiving Methadone Substitution

Abstract: The usefulness of beta-hexosaminidase (uHex) and gamma-glutamyltransferase (uGGT) activity in urine as markers of chronic alcohol abuse was examined in male methadone programme participants. The group consisted of 24 non-abusing and 21 alcohol-abusing men. It has been demonstrated that the uHex test is one of the best alcohol abuse markers for opiate-dependent individuals (Receiver Operating Characteristic (ROC) area under the curve (AUC) 0.82, sensitivity 0.70, specificity 0.82). The uGGT test can be used as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
5
0

Year Published

2004
2004
2006
2006

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 27 publications
2
5
0
Order By: Relevance
“…The present study confirmed the results of our preliminary work on uHex utility in alcohol-dependent men (21,22), and showed negligible bias from endogenous inhibitors of the enzyme. This finding and the slightly, albeit non-significantly, higher AUC value ( Table 2) mean that uHex is superior to eAAP as a possible clinical marker.…”
Section: Markersupporting
confidence: 93%
See 4 more Smart Citations
“…The present study confirmed the results of our preliminary work on uHex utility in alcohol-dependent men (21,22), and showed negligible bias from endogenous inhibitors of the enzyme. This finding and the slightly, albeit non-significantly, higher AUC value ( Table 2) mean that uHex is superior to eAAP as a possible clinical marker.…”
Section: Markersupporting
confidence: 93%
“…Factor analysis of the markers studied revealed that the liver and kidney origins of the markers were independent factors, and showed significant correlation within, but not between, the two marker groups. These findings indicate that these marker groups represent metabolically unrelated events, which is in agreement with previous studies (20)(21)(22)(23) and suggests that combining representatives of these marker groups would be of diagnostic advantage. This indication was confirmed by the stepwise discriminant analysis, which showed highest diagnostic potential for the combination of GGT and uHex data into a composite marker and no significant gain from adding any of the remaining markers to this combination.…”
Section: Markersupporting
confidence: 91%
See 3 more Smart Citations